Perancangan dan Pengembangan Media Pembelajaran Interaktif Berbasis FlipBook pada Mata Pelajaran Teknik Elektronika Industri untuk Materi Elemen Sistem Kontrol Industri - Reza, Bayu Rizky Alfa; Efrizon, Efrizon; Dewi, Ika Parma; Anori, Sartika (Lembaga Yasin AlSys, 2025)
This study aims to (1) design an interactive media-based learning tool using FlipBook for the subject of Industrial Electronics Engineering, specifically on the topic Elements of Industrial Control Systems, and (2) evaluate the validity and practicality of the developed learning media. The research was conducted with Grade XI students at SMK Negeri 5 Padang, utilizing the 4-D development model, which includes the stages of Define, Design, Develop, and Disseminate. Data were collected in both qualitative and quantitative forms through questionnaires and analyzed using descriptive quantitative methods. The results show that the FlipBook-based interactive learning media covers four core content elements related to Elements of Industrial Control Systems. Expert evaluations indicate that the media has a very high level of validity, with an average score of 90%. Although the media was deemed feasible and effective, some limitations were identified in its implementation by instructors, particularly regarding technical readiness and integration into the learning process. The study concludes that FlipBook media holds great potential as an interactive learning tool in vocational education. However, further development is needed, especially in conducting needs analysis and designing adaptive content tailored to real classroom conditions.